2019
DOI: 10.1177/1729881419885696
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization of a lightweight rocker–bogie rover for ocean worlds applications

Abstract: Relatively recent discoveries have shown that large quantities of water can be found on moons of some of the planets among the gas giants in our solar system. Robotic mobility systems can study the varied geology and origins of these bodies if they are able to navigate the complex terrains of ocean worlds. The topographical features of ocean worlds present a unique combination of challenges for mobility. These include cryogenic ice, penitentes, salt evaporites, chaotic regions, and regolith with uncertain shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Surface mobility for a mission to an icy world would enhance science return multi-fold, in addition to avoiding contamination and enabling increased confidence for difficult measurements such as those for life detection. Recent technology advancements demonstrate multiple types of mobility (i.e., hopper (Hockman et al 2016, Meirion-Griffith et al 2019, wheeled rover (Nayar et al 2019), snake-like (Ono et al 2019, an actively articulated wheel-on-limb rover (Reid et al 2019), and a steam-propelled hopper (Meirion-Griffith et al, 2019)) that could be appropriate for most terrains identified on icy worlds. We encourage NASA to consider such architectures to maximize capability and science return on future missions to Enceladus, Europa, Triton and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…Surface mobility for a mission to an icy world would enhance science return multi-fold, in addition to avoiding contamination and enabling increased confidence for difficult measurements such as those for life detection. Recent technology advancements demonstrate multiple types of mobility (i.e., hopper (Hockman et al 2016, Meirion-Griffith et al 2019, wheeled rover (Nayar et al 2019), snake-like (Ono et al 2019, an actively articulated wheel-on-limb rover (Reid et al 2019), and a steam-propelled hopper (Meirion-Griffith et al, 2019)) that could be appropriate for most terrains identified on icy worlds. We encourage NASA to consider such architectures to maximize capability and science return on future missions to Enceladus, Europa, Triton and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…The wheels of space rovers, adopted for Mars missions, are made of an aluminum alloy rim, with protruding cleats, connected to the hub by means of curved spokes in titanium alloy [21]. By choosing appropriate shapes and sizes of the components, the wheel will have a desired radial deformability and a desired extension of the patch contact area, as it happens for tired vehicle where the extension of the patch area is due to the radial deformability of the tire.…”
Section: Wheel Traction Forcementioning
confidence: 99%
“…The typical six-wheeled, rocker-bogie, or similar suspensions have been discussed at length in the literature with optimization studies [8] and traverse characterization [3]. Linkage differential mechanisms are fixed on either side of a rover to balance the angle of the left and right sides.…”
Section: Modified Wheeled Travelmentioning
confidence: 99%